A Study on Oscillatory and Asymptotic Nature of Impulsive Neutral Differential Equations of Order Three (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider a class of third-order neutral impulsivedifferential equations. An equivalent class of neutral differential equations isobtained by using a suitable substitution. Some new oscillation results areproved. Moreover, we discuss the asymptotic behavior of the solution. Theresults presented here are illustrated via examples.
Keywords: Neutral differential equations; Impulsive conditions; Oscillation criteria; Asymptotic behavior.